Studying the self-assembly of networks of conjugated oligomers - Lim, Zheng Bang (2012)
Two new tetrahedral symmetric core units (p-type 1 and n-type 2) for forming organic supramolecules were successfully synthesized. They were then self-assembled by Zn(II)–coordination to form new 3D supramolecular networks S1 and S2 which could be disassembled by adding more Zn(II) ions and re-self-assembled to form extended 3D networks S3–6 after inserting linear linking units (p-type 26 or n-type 27) into. Energy transfer between core and linker units was observed in S4 and S6 who emit red fluorescence with the emission coming from the benzothiadiazole linker unit (n-type) within the networks due to its lower bandgap. S1–6 are insoluble in any organic solvents at room temperature. They are found to be relatively amorphous and non-porous (highly interpenetrating) based on their XRD and BET results, respectively. CdSe nanoparticles were successfully incorporated in S3 and S4 to form new nancomposites S3 (with CdSe) and S4 (with CdSe) which were evaluated by TEM and XRD. Same dialkoxybenzothiadiazole (acceptor) was combined with different types of thiophene-based monomers (donors, D) under Stille reaction to form new D–A π-conjugated organic copolymers P1–4 with low bandgaps, proving the substituted benzothiadiazole was a good n-type unit. A PCE result of over 1% has been obtained from a photovoltaic device using P4 combined with PCBM. As well as these covalently linked organic polymers, Zn(II)–coordinated self-assembled metallopolymers were produced including two metallo-homopolymers P5 (p-type), P6 (n-type) and a metallo-alt-copolymer (p-type-alt-n-type) (P7). They are soluble in highly polar aprotic solvents and hence can be used as models to compare with the insoluble networks S1–6. The electro-optical properties of the monomers as well as of the metallopolymers are strongly influenced by the nature of the attached π-conjugated spacer unit. P7 featured an energy transfer from the donor to the acceptor unit (substituted benzothiadiazole) and this acceptor unit acted as sole emissive unit to produce red fluorescence from the polymers due to its lower bandgap.